2019
DOI: 10.3390/ma12010171
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Surface Finisher of Car Park Slab Using Waterborne Silicon Acrylic with Polyamide [Part I: Performance Evaluation]

Abstract: A waterborne coating system for car park slab has recently gained interest as an alternative for solvent-based finishing materials due to environmental concerns and prolongation of service life. However, water-based finishers, regardless of their eco-friendly properties, have relatively lower hardness compared to traditional finishing systems. In order to overcome this obstacle, a hybrid technology was used to develop a substitute surface finisher for car park slab and its performance was evaluated according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…According to Table 9 , it can be found that the gloss of the two kinds of coating with microcapsules was similar, but the hardness and impact resistance of the coating with epoxy resin microcapsules were relatively high, while the adhesion was low. In Table 9 , the core–wall ratio of epoxy resin microcapsule is 0.83:1, which is higher than that of waterborne acrylic microcapsules (0.58:1), and the hardness of waterborne acrylic is relatively low [ 32 ]. Therefore, the hardness of the coating prepared by epoxy resin microcapsules is higher than that of waterborne acrylic microcapsules.…”
Section: Resultsmentioning
confidence: 99%
“…According to Table 9 , it can be found that the gloss of the two kinds of coating with microcapsules was similar, but the hardness and impact resistance of the coating with epoxy resin microcapsules were relatively high, while the adhesion was low. In Table 9 , the core–wall ratio of epoxy resin microcapsule is 0.83:1, which is higher than that of waterborne acrylic microcapsules (0.58:1), and the hardness of waterborne acrylic is relatively low [ 32 ]. Therefore, the hardness of the coating prepared by epoxy resin microcapsules is higher than that of waterborne acrylic microcapsules.…”
Section: Resultsmentioning
confidence: 99%
“…Block pavements constructed of natural stones are often required the specific areas where are in low traffic volumes such as communal sites, sidewalks, and historically neighbourhood areas [1][2][3]. Commonly, stone-paved roads are quarried in heritage sites or cities due to their variety in creation (patterns, texture, and environmental aspects) [1,[4][5][6][7][8][9]. However, the deteriorations of those types of pavements have frequently occurred because of the increasing amount and weight of vehicles crossing.…”
Section: Introductionmentioning
confidence: 99%